2020
DOI: 10.1016/j.ijid.2020.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical characteristics of cases of SARS-CoV-2 infection with abnormal imaging findings

Abstract: J o u r n a l P r e -p r o o f 2 (Lanjuan Li); yidayang65@zju.edu.cn (Yida Yang) Highlight  COVID-19 has be a great threat to world health.  We aim to investigate clinical features of patients with abnormal imaging findings.  Those with abnormal images have more obvious clinical and laboratory features.  Combing clinical data with imaging score can predict severe/critical type. AbstractPurpose: To investigate the epidemiological, clinical characteristics of COVID-19 patients with abnormal imaging findings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
246
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(277 citation statements)
references
References 27 publications
14
246
0
17
Order By: Relevance
“…A total of 907 studies were retrieved through the search, of which 19, 8-26 16 from China, 1 from Korea, and 2 from the United States, included data on smoking behavior and COVID-19 disease progression (Supplementary Table S1). Seventeen studies [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26] were based on hospitalized patients and two 8,13 included both hospitalized patients and outpatients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 907 studies were retrieved through the search, of which 19, 8-26 16 from China, 1 from Korea, and 2 from the United States, included data on smoking behavior and COVID-19 disease progression (Supplementary Table S1). Seventeen studies [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26] were based on hospitalized patients and two 8,13 included both hospitalized patients and outpatients.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure group for our analysis were those who had a history of smoking (current smokers or former smokers) and unexposed group was never smokers. Nine studies 10,12,14,18,20,21,23,25,26 assessed whether the patient was a "current smoker," five studies 8,9,13,16,24 assessed whether the patient was a current or former smoker (as separate categories), and five studies 11,15,17,19,22 assessed whether the patient had a "history of smoking" (current or former).…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] Prevalent headache in severe cases (17%) versus 10% in milder cases, reported by a recent study from Wuhan, could suggest the inflammation and hypoxia correlated with the disease severity may take a part. 1,4 Recently, it was also reported that compared with non-ICU COVID-19 patients, ICU patients had higher plasma levels of IL-2, IL-7, IL-10, G-CSF, IP-10, MCP1, MIP1A, and TNF. 8 Moreover, it is known that pyrogenic fever involves inflammatory mediators in the hypothalamus containing cytokines, glutamate, PGE 2 , NO, and reactive oxygen species; besides the principal cells in this part, microglia, macrophages, astrocytes, blood brain barrier, and endothelial cells.…”
Section: Angiotensin II (Ang Ii) Produced By Ace Acts Through At1mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] A recent meta-analysis (n = 3598 patients) and a handful of reports disclosed that headache is among the COVID-19-related symptoms with a rate mostly around 11%-14%, in patients who had either died or recovered. [3][4][5] A higher rate reported was 34% from Zhejiang province, China in a small series of 62 patients with a milder course compared to Wuhan, but no further details about the characteristics of the headache or prior headache history were given. 6 In a series of 262 confirmed cases of the COVID-19 in Beijing, the most common symptoms at the onset of illness were cited as fever, cough, fatigue, and dyspnea followed closely by headache with a rate of 6.5%.…”
mentioning
confidence: 99%
“…We read with interest the commentary by Sun detected, but 12 were excluded as duplicates and three because of lacking data; two further articles were retrieved from reviewing the reference lists, and therefore, six articles were enrolled for analysis. [2][3][4][5][6][7] Standardized mean differences (SMD) were used to build forest plots of continuous data and to evaluate differences in bilirubin levels. P < .05 was considered statistically significant, and 95% confidence intervals (CIs) were reported.…”
Section: Dear Editormentioning
confidence: 99%